Formulasi, Evaluasi Sensori Dan Komposisi Gizi Food Bar Berbasis Pisang Dan Tepung Jagung Tinggi Mineral Sebagai Alternatif Pangan Darurat - Ameliyah, Rantika Yesi; Hervidea, Radella; Puteri, Hidayatusy Syukrina (Journal of Pharmaceutical and Sciences, 2025)
Background: As a disaster-prone country, Indonesia requires emergency food that meets the nutritional needs of disaster victims. This study develops a food bar based on local ingredients of kepok banana (Musa paradisiaca) and corn flour as a mineral-rich emergency food alternative. Objective: The research aims to analyze the optimal formulation, sensory evaluation, and nutritional composition of banana and corn flour-based food bars as emergency food products. Methods: This experimental study used a Completely Randomized Design (CRD) with three different formulations: F1 (80% banana + 20% corn flour), F2 (70% banana + 30% corn flour), and F3 (20% banana + 80% corn flour). Sensory testing involved 25 panelists evaluating color, aroma, taste, and texture. Data analysis used the Kruskal-Wallis test and Dunn's test, while nutritional composition was analyzed through proximate analysis and potassium testing using Atomic Absorption Spectrophotometry (AAS). Results: The results showed significant differences (p<0.05) in color, taste, and texture parameters, but not in aroma (p>0.05). Formulation F1 received the highest scores for taste (3.52) and texture (2.88). Proximate analysis revealed F1 had the highest water content (6.50%) and crude fiber (4.51%), while F3 had the highest carbohydrate content (72.62%). The potassium content of F1 reached 7.13 mg/g, meeting 10-11% of the daily RDI per 50g food bar. Conclusion: Formulation F1 (80% banana + 20% corn flour) is the best choice as emergency food due to its good sensory acceptance and complete nutritional content, particularly its potassium content which is crucial for emergency conditions.